PERSESPSI TERHADAP KEPUASAN HIDUP GURU SEKOLAH LANJUTAN - Siti Partini Suardiman (Universitas Negeri Yogyakarta, 2000)
This study tried b rtnd logyakarta oat the degree of teacher life satisfaction and its interactionwith their age, gender, and level of education. Researeh subject of this study were participants of creativity training teachers. Questionnaire personal background. It was for secondary school was used to reveal the life satisfaction and found that most of the creativity training alumni of the secondary teachers perceived they had a high life satisfaction rank from future. The highest were: psychological satisfaction and in Independent variables such as age, gender, and level of education turned out only level of education, that has a correlation with life satisfaction. Most of the subject have part time job and that might explain on their solution to the fact that teacher's salary is relatively low.